Askin tumor of thoracopulmonary region in a child: Case report and literature review. Issue 1 (February 2016) - Cremone, G.; D'Amora, M.; Rossi, E.; Zeccolini, R.; Coppola, S.; Zeccolini, M.
Abstract: Askin tumor is an uncommon malignant neoplasm of the thoracopulmonary region mainly occurring in children and adolescents. In this case, Computed Tomography (CT 1 ) imaging features of Askin tumor and differential diagnosis criteria with others possible chest neoplasms are presented. Highlights: CT represents the essential imaging technique for Askin tumor's diagnosis. Chest Radiography is not a specific exam for Askin tumor. CT is a very useful tool in the differential diagnosis. MPR CT study can better demonstrate the tumor response to therapy.